Analysis of Gene Signatures of Tumor Microenvironment Yields Insight Into Mechanisms of Resistance to Immunotherapy - Wang, Ben; Liu, Mengmeng; Ran, Zhujie; Li, Xin; Li, Jie; Ou, Yunsheng (Frontiers in Bioengineering and Biotechnology, 2020)
Background: The recent clinical success of immunotherapy represents a turning point in cancer management. But the response rate of immunotherapy is still limited. The inflamed tumor microenvironment has been reported to correlate with response in tumor patients. However, due to the lack of appropriate experimental methods, the reason why the immunotherapeutic resistance still existed on the inflamed tumor microenvironment remains unclear. Materials and Methods: Here, based on single-cell RNA sequencing, we classified the tumor microenvironment into inflamed immunotherapeutic responsive and inflamed non-responsive. Then, phenotype-specific genes were identified to show mechanistic differences between distant microenvironment phenotypes. Finally, we screened for some potential drugs that can convert an unfavorable microenvironment phenotype to a favorable one to aid current immunotherapy. Results: Multiple signaling pathways were phenotypes-specific dysregulated. Compared to non-inflamed microenvironment, the expression of interleukin signaling pathways-associated genes was upregulated in inflamed microenvironment. Compared to inflamed responsive microenvironment, the PPAR signaling pathway-related genes and multiple epigenetic pathways-related genes were, respectively, suppressed and upregulated in the inflamed non-responsive microenvironment, suggesting a potential mechanism of immunotherapeutic resistance. Interestingly, some of the identified phenotype-specific gene signatures have shown their potential to enhance the efficacy of current immunotherapy. Conclusion: These results may contribute to the mechanistic understanding of immunotherapeutic resistance and guide rational therapeutic combinations of distant targeted chemotherapy agents with immunotherapy.